Analiza lingwistyczna pieśni polskojęzycznych ze wsi Murowana Oszmianka - Kaspiarovich, Karalina (Slavia Occidentalis, 2023)
The subject of the article is an analysis of the lyrics of 13 Polish songs sung in the village of Muravanaya Ashmyanka. A linguistic analysis of the transcribed lyrics of the songs based on the author’s personal recordings, conducted according to dialectological publications, and carried out on the phonetic, morphological, syntactic, and lexical levels, revealed numerous clear influences of the East Slavic languages. Among the many deviations from the general Polish language, and the multitude of dialectal features characteristic of the Northern Borderlands dialect, the following may be concluded: asynchronous pronunciation of nasal vowels at the final position and before fricative consonants, vowel reduction, the pronunciation of the dental consonant ł, the occurrence of the prepositional construction instead of the general Polish synthetic one, preservation of the voiced quality of the consonant w after voiceless consonants, soft pronunciation of l, change of grammatical gender, voiced pronunciation of the consonanth. The lyrics of the collected and transcribed songs are an example of valuable linguistic material fading into oblivion with the passage of time.